2001
DOI: 10.1037/0022-0167.48.3.310
|View full text |Cite
|
Sign up to set email alerts
|

Social connectedness, dysfunctional interpersonal behaviors, and psychological distress: Testing a mediator model.

Abstract: The study examined the relationship among social connectedness, dysfunctional interpersonal behaviors, and psychological distress. The authors specifically hypothesized that the direct negative effect of social connectedness on psychological distress would be mediated by dysfunctional interpersonal behaviors. Prior to testing the hypothesis, the authors revised the original Social Connectedness Scale (SCS; R. M. Lee & S. B. Robbins, 1995). Studies 1 and 2 describe the revision and validation of the SCS on sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
567
1
23

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 639 publications
(607 citation statements)
references
References 31 publications
16
567
1
23
Order By: Relevance
“…They think of themselves as pariahs and are others often misunderstand them as they separate themselves from society and face ample challenges in the social world (Denial, 2009). Although people in the latter type eventually manage to develop relationships with groups, they almost always lack an in-depth connection with themselves as well as with others (R. Lee, Draper, & S. Lee, 2001). Thus researchers advocate the notion that social connectedness is a primary life aspect as it has been revealed to be related to higher levels of well-being in adolescents (Griffiths et al, 2007), the older generation (Fiori, Antonncci, & Cortina, 2006;Litwin, 2001).…”
Section: Social Connectednessmentioning
confidence: 99%
See 1 more Smart Citation
“…They think of themselves as pariahs and are others often misunderstand them as they separate themselves from society and face ample challenges in the social world (Denial, 2009). Although people in the latter type eventually manage to develop relationships with groups, they almost always lack an in-depth connection with themselves as well as with others (R. Lee, Draper, & S. Lee, 2001). Thus researchers advocate the notion that social connectedness is a primary life aspect as it has been revealed to be related to higher levels of well-being in adolescents (Griffiths et al, 2007), the older generation (Fiori, Antonncci, & Cortina, 2006;Litwin, 2001).…”
Section: Social Connectednessmentioning
confidence: 99%
“…Thus, it can be contended that there are several factors that predict the outcomes and success of adolescent academic performance (Barber & Rollins, 1990;Barnes & Farrell, 1992;Pajares, 1997;Fremd & Baltes, 2002;Joo, Bong & Choi, 2000;Lee & Robbins, 2000). In addition to this, there had been extensive studies concerning issues of psycho-social and cognitive factors and adolescent development, which related various aspects of such factors to several outcomes (Lee & Robbins, 2000; R. Lee, Draper, & S. Lee, 2001;Zimmerman, 2000;Mansfield, 2010;Chemers et al, 2001;Megan, 2009).…”
mentioning
confidence: 99%
“…The (large) gender difference in sensitivity to others, measured with the ACS-30 (Bekker and van Assen 2006), the measurement instrument of autonomy-connectedness we also employ in this study, has repeatedly and consistently been found in non-random, rather specific samples. Among the populations investigated were college students (e.g., Bekker and van Assen 2006; see also Lee et al 2001), primary health care patients (Bekker and Belt 2006), participants of work stress prevention training , and women suffering from eating or anxiety disorders (Bekker 1993;Bekker et al under review). Further research on autonomy-connectedness, gender differences and psychopathology will be aided by more firm empirical evidence for gender differences in sensitivity to others.…”
Section: Clinical Relevance Of Autonomy-connectednessmentioning
confidence: 99%
“…In many cases, autonomy is considered as the opposite of connectedness; because women compared with men are often ascribed higher levels of connectedness (e.g., Lee et al 2001;Taylor et al 2000;Nolen-Hoeksema and Jackson 2001), they are then automatically also lower in autonomy. But what is connectedness, and what gender differences have been reported in this domain?…”
mentioning
confidence: 99%
“…Social connectedness is measure by means of a questionnaire that has been derived from Social Connectedness Scale Revised (SCS_R) questionnaire [12]. The results about the social connectedness is reported in [13].…”
Section: Discussionmentioning
confidence: 99%